Biodegradable flocculant of chitosan grafted acrylamide synthesized by redox technique for textile wastewater treatment /cNurhayati Izad Abdul Aziz - Nurhayati Izad Abdul Aziz, 1989-, author; Norzita Ngadi; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteran (Kimia)) - Universiti Teknologi Malaysia, 2012